Characteristics of Kidney Cancer Patients At Hasan Sadikin Hospital, Bandung - Ardiansyah, Novan; Safriadi, Ferry (Indonesian Journal of Cancer, 2023)
Background:  Kidney cancer accounts for 5% and 3% of all malignancies in men and women, respectively, representing the 7th most common cancer in men and the 10th most common cancer in women. In Asia, especially in Indonesia, the incidence of kidney cancer has not been widely reported. Therefore, researchers intend to investigate the characteristics of Kidney Cancer at Hasan Sadikin Hospital, Bandung, during the period 2015–2019. Methods: This research is a descriptive retrospective study taken from the medical records of patients with kidney cancer in the Department of Urology, Universitas Padjadjaran, Hasan Sadikin Hospital. The study was conducted from June 2019 until all the medical record data for the sample were fulfilled. The data included age, gender, and histopathological findings. Results: From the data collection, it was found that there were a total of 126 patients with kidney cancer, occurring in 83 male patients (65.8%) and 43 female patients (34.2%). The age group 0–10 years dominated the occurrence of kidney cancer, with 32 out of 126 patients (25.4%), followed by the 41–50 age group with 30 patients (23.8%), and the 21–30 age group had the fewest diagnoses of kidney cancer. A total of 78 patients (61.9%) were diagnosed with Renal Cell Carcinoma (RCC). Clear cell RCC was more common, with 64 cases (50.7%), compared to papillary RCC with 13 cases (10.3%) and Chromophobe RCC with 1 case (0.8%). The most commonly found kidney cancer was Wilm’s tumor, with 33 patients (26.1%), occurring in individuals under 20 years of age. Conclusion: This study found that kidney cancer is more common in males than in females. RCC is the most frequently diagnosed type, with clear cell subtype being predominant, especially in patients over 40 years of age. Wilm’s tumor dominates kidney cancer cases in individuals under 20 years of age.